How energy and chemistry converge for a fossil-free future - Mertens, Jan; Breyer, Christian; Belmans, Ronnie; Gendron, Corinne; Geoffron, Patrice; Fischer, Carolyn; Du Fornel, Elodie; Ledent, Olivier; Lester, Richard; Nicholas, Kimberly A. ; 0000-0002-4756-7851; Megrelis, Laura; de Miranda, Paulo Emilio Valadão; et al. (iScience, 2025)
The chemical industry must undergo a dual transformation: electrifying energy use and defossilizing carbon feedstocks. This paper, developed by ENGIEs Scientific Council, examines how energy and chemistry can converge to enable this shift. We assess the roles of biomass, recycled plastics, and CO2 as sustainable carbon sources and explore the enabling potential of electrification, low-carbon hydrogen, and direct air capture. Novel process pathways and infrastructure scenarios are analyzed to highlight strategic opportunities for cross-sectoral collaboration. Our findings underscore the need for coordinated investment, policy support, and alignment with renewable energy geography to achieve a resilient, fossil-free future.
Publisher Copyright: © 2025
Keywords: earth sciences; energy policy; energy resources; energy sustainability; energy systems